중년여성의 견갑통 통증완화를 위한 부항과 뜸 겸용요법의 적용효과 - 김이순(Yi Soon Kim); 김귀분(Kwuy Bun Kim); 김경철(Gyeong Cheol Kim); 김영희(Young Hee Kim) (동의생리병리학회지, 2009)
This study is to determine the effects of BUDDEUMI(moxibustion and cupping a boli) therapy on the relief of shoulder pain among middle aged women. methods : A total of 39 middle aged women with shoulder pain are selected : 20 in the experimental group and 19 in the control group. The data was collected by using questionnaires. The BUDDEUMI(moxibustion and cupping a boli) therapy on the should and back was administered to the experimental group, and no treatment was given to the control group. All of the subjects were examined on a subjective symptom scale and on the grade of discomfort and pain in everyday life as developed by Japan's Industrial Fatigue Research Committee of the Industrial Hygienics Society(1988), Sohn, Mong Ho(1999), Visual Analogue Scale as developed by Cline (1992). SPSS/win 12.0 was used for Date analysis, General features demonstrated by frequency number and percentage. The effects of the BUDDEUMI(moxibustion and cupping a boli) therapy was analyzed by a t-test. The homogeneity testing revealed that all study variables are equally distributed between experimental and control groups. The hypothesis, 'the experimental group who received BUDDEUMI(moxibustion and cupping a boli) therapy will decrease in the grade of discomfort of shoulder', is supported. The hypothesis, 'the experimental group who received BUDDEUMI(moxibustion and cupping a boli) therapy will decrease in the Visual Analogue Scale is supported. Conclusion : As a result of this study, BUDDEUMI(moxibustion and cupping a boli) therapy will be able to be used as the self care therapy to improve the symptoms of middle aged women who has the shoulder pain.